Planning GDR and Czechoslovakia : The Scale Question under State Socialism - Azmah, Arzmi (Routledge, 2022)
This contribution delves into how former European socialist countries defined urban planning and their respective development strategies. It reveals local perspectives on how the planning process operated, thus unfolding the unique trajectory in the post-socialist path of each city based on its location and importance within the country. The aim of this chapter is to juxtapose the particularities of planning practices in Czechoslovak Socialist Republic (ČSSR) with the German Democratic Republic (GDR) to explain the implications in urban development in terms of how they approach planning from different scales. Drawing from an examination of sources obtained from national archives, educational institutions and architectural journals from the former GDR and ČSSR, as well as various interpretations from various secondary literature, the findings conclude that ČSSR had a larger, sectoral, stratified approach to planning their cities whereas the city of East Berlin was planned on a smaller scale. As a result, there were more integration of public transport services, infrastructure and the idea of the compact city was more dominant in East Berlin compared to Bratislava and Prague, which became more auto-oriented and deconcentrated as the result of the Czechoslovak highway network policy, due to the ČSSR's more sectoral fragmented approach.